Postoperative pain after colorectal surgery - Lindberg, Margaretha (Int J Colorectal Dis, 2020)
PURPOSE: Postoperative pain is a keystone in perioperative programs, as pain negatively impacts recovery. This study aimed to evaluate pain after elective colorectal surgery and to identify risk factors for postoperative pain. METHODS: This prospective cohort study comprised consecutive patients undergoing elective colorectal surgery within the Enhanced Recovery after Surgery (ERAS) perioperative program between March 2013 and April 2017. The numeric rating scale (NRS) was used to estimate maximum pain. Logistic regression was used to model associations with the type of surgery, age, gender, and comorbidities. RESULTS: The cohort comprised 434 of 459 eligible patients. On the day of surgery to postoperative day 3, 50–64% of patients reported moderate to severe pain (NRS 4–10). Postoperative pain was similar for open and minimally invasive rectal surgery, while patients undergoing minimally invasive colonic surgery experienced more pain on the day of surgery and less pain on postoperative days 2 and 3 vs. open colonic surgery. Younger age was associated with more pain every postoperative day and by 0.7 NRS/10 years (95% CI 0.5–0.9, P < 0.001) on the day of surgery, while having diabetes type 2 was associated with less postoperative pain by − 1.3 NRS (95% CI − 2.4 to − 0.2) on the day of surgery. CONCLUSIONS: The majority, and young patients in particular, experience moderate to severe pain after open and minimally invasive colorectal surgery, despite following ERAS perioperative program. There is a need for effective and individualized analgesia after colorectal surgery, since the individual pain response to surgery is difficult to predict.